Effects of surface and grain boundary on temperature-pressure nano-phase diagrams of nanostructured carbon. (15th January 2022) - Yao, Xue; Liu, Guo-Jun; Lang, Xing-You; Li, Hong-Dong; Zhu, Yong-Fu; Jiang, Qing
Abstract: Temperature-pressure phase diagrams can provide guidance for materials preparation and application, but nano-phase diagrams are scarce. Coordination environment of atoms located at surface and grain boundary differs to that of interior ones, indicating non-negligible surface and grain boundary effects on nano-phase transitions. The surface effect was universally considered in previous theoretical models, but its size-dependence was ignored. Moreover, the grain boundary effect was rarely explored. Here, the surface and grain boundary effects are modeled using a thermodynamic approach to construct the nano-phase diagrams of nanostructured carbon. As the size is reduced, additional pressures induced by these two effects rise, contributing to the transition from thermodynamically stable phase to metastable one, and the phase boundary shifts to low temperature and low pressure. Our prediction agrees well with available literature results. Graphical Abstract: Image, graphical abstract